1995
DOI: 10.1084/jem.182.5.1337
|View full text |Cite
|
Sign up to set email alerts
|

Migration of monocytes across endothelium and passage through extracellular matrix involve separate molecular domains of PECAM-1.

Abstract: SummaryDuring the inflammatory response, the adhesion molecule PECAM plays a crucial role in transendothehal migration, the passage of leukocytes across endothelium. We report here an additional role for PECAM in the subsequent migration of monocytes through the subendothelial extraceHular matrix. PECAM has six immunoglobulin (Ig) superfamily domains. Monoclonal antibodies whose epitopes map to domains 1 and/or 2 selectively block monocyte migration through the endothelial junction, whereas those that map to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
208
3
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(223 citation statements)
references
References 26 publications
10
208
3
1
Order By: Relevance
“…Furthermore, in agreement with previous findings, 15,22 PECAM-1 Ϫ/Ϫ mice exhibited a defect in neutrophil emigration through the vascular BM. Some previous studies have observed a role for PE-CAM-1 in migration through the endothelium as opposed to the BM, 44,45 but this was only seen when antibodies against specific domains of PECAM-1 were used, as opposed to full genetic deletion of the protein as with this work. Collectively, the present findings provide the first evidence to demonstrate that the adhesion molecules ICAM-2, JAM-A, and PECAM-1 can act in sequence to mediate distinct but sequential steps in supporting neutrophil emigration from the vascular lumen to the extravascular tissue ( Figure 6B).…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, in agreement with previous findings, 15,22 PECAM-1 Ϫ/Ϫ mice exhibited a defect in neutrophil emigration through the vascular BM. Some previous studies have observed a role for PE-CAM-1 in migration through the endothelium as opposed to the BM, 44,45 but this was only seen when antibodies against specific domains of PECAM-1 were used, as opposed to full genetic deletion of the protein as with this work. Collectively, the present findings provide the first evidence to demonstrate that the adhesion molecules ICAM-2, JAM-A, and PECAM-1 can act in sequence to mediate distinct but sequential steps in supporting neutrophil emigration from the vascular lumen to the extravascular tissue ( Figure 6B).…”
Section: Discussionmentioning
confidence: 57%
“…In addition, circulating antibodies to PECAM prevented emigration of leukocytes in vivo following an inflammation stimulus (Bogen et al, 1994). Continued leukocyte migration through sub-endothelial extracellular matrix also involves PECAM, utilizing a separate heterophilic binding domain distinct from that used to traverse endothelial cells (Liao et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Another molecule expressed at the borders between confluent endothelial cells and on the surface of most leukocytes, CD99, could also be involved (Schenkel et al, 2002). PECAM seems also to be involved in the subsequent diapedesis across the subendothelial environment but requiring heterophilic binding to an unidentified ligand (Liao et al, 1995). In addition, release of neutrophil-derived proteases is also needed for this latest step (Duncan et al, 1999).…”
Section: Molecular Mechanisms That Control Leukocyte Extravasationmentioning
confidence: 99%